A large prospective investigation of outdoor light at night and obesity in the NIH-AARP Diet and Health Study - Dong Zhang; Rena R. Jones; Tiffany M. Powell-Wiley; Peng Jia; Peter James; Qian Xiao (Environmental Health, 2020)
Abstract Background Research has suggested that artificial light at night (LAN) may disrupt circadian rhythms, sleep, and contribute to the development of obesity. However, almost all previous studies are cross-sectional, thus, there is a need for prospective investigations of the association between LAN and obesity risk. The goal of our current study was to examine the association between baseline LAN and the development of obesity over follow-up in a large cohort of American adults. Methods The study included a sample of 239,781 men and women (aged 50–71) from the NIH-AARP Diet and Health Study who were not obese at baseline (1995–1996). We used multiple logistic regression to examine whether LAN at baseline was associated with the odds of developing obesity at follow-up (2004–2006). Outdoor LAN exposure was estimated from satellite imagery and obesity was measured based on self-reported weight and height. Results We found that higher outdoor LAN at baseline was associated with higher odds of developing obesity over 10 years. Compared with the lowest quintile of LAN, the highest quintile was associated with 12% and 19% higher odds of developing obesity at follow-up in men (OR (95% CI) = 1.12 (1.00, 1.250)) and women (1.19 (1.04, 1.36)), respectively. Conclusions Our findings suggest that high LAN exposure could predict a higher risk of developing obesity in middle-to-older aged American adults.